Estetika Jepang Wabi-Sabi dan Mono no Aware dalam Film Memories of Matsuko tahun (2006) - Armansyah, Bau Shafira; Astuti, Meta (Japanology: The Journal of Japanese Studies, 2023)
The film "Memories of Matsuko" (2006), directed by Tetsuya Nakashima from Japan, explores the tragic life of its main character, Matsuko, and features a unique dramatic narrative enriched by diverse Japanese visual aesthetics. This study aims to reveal how Japanese aesthetics are reflected in the film, particularly through themes of sadness and suffering articulated in the narrative and visual elements. A qualitative approach with descriptive analytical methods was employed, involving stages such as a literature review on Japanese aesthetics, in-depth analysis of the film focusing on Keene's (1969) theories of wabi-sabi and mono no aware, and the compilation of research findings. The results indicate that Japanese aesthetics such as wabi-sabi and mono no aware are subtly reflected in the film's thematic scenes, which are dominated by emotional complexity and the situations experienced by the protagonist, Matsuko. Through these aesthetics, the beauty in imperfection and the ephemerality of elusive happiness are revealed. Moreover, the film presents conflict and resolutions not through dramatic outbursts, but through calm expressions and acceptance of bitter realities. This reflects the interaction between beauty and functionality in Japanese aesthetics. The integration of Japanese aesthetics along with its paradoxes offers a more varied perspective in depicting the tragedy experienced by its character.